Superoxide dismutase activity and expression in human venous and arterial bypass graft vessels. - Guzik, T; Olszanecki, R; Sadowski, J; Kapelak, B; Rudziński, P; Jopek, A; Kawczynska, A; Ryszawa, N; Loster, J; Jawien, J; Czesnikiewicz-Guzik, M; Channon, K; et al. (2005)
UNLABELLED: Venous bypass grafts are more prone to accelerated atherosclerosis than arterial grafts, which is partly related to increased oxidative stress and diminished nitric oxide bioavailability. In veins superoxide production is dependent primarily on nox2 NAD(P)H oxidase expression, while in arteries nox4 appears to play an important role. This may in part explain differences in susceptibility to graft failure. Net levels of oxidative stress are however determined in parallel by the production as well as by degradation of free radicals (eg. by superoxide dismutases, catalases, thioredoxins etc). The differences in superoxide dismutase (SOD) expression and activity in human bypass conduit vessels remain unclear. Accordingly, we aimed to compare SOD activity and protein levels as well as its functional effects on superoxide production in segments of human internal mammary arteries (IMA) and saphenous veins (HSV) from patients undergoing bypass graft surgery (n=24). SOD activity was assessed by inhibition of pyrogallol autoxidation, Cu-Zn SOD and Mn SOD protein levels were studied by immunoblotting. Basal superoxide release was detected by lucigenin (5 microM) enhanced chemiluminescence. Total SOD activity did not differ significantly between HSV and IMA. Similarly, no difference was observed in SOD activity in the presence of KCN (Mn-SOD). Human bypass conduit vessels show amounts of Cu-Zn SOD or Mn-SOD protein levels. In both HSV and IMA segments superoxide production was more than doubled in the presence of SOD inhibitor-DETC. CONCLUSIONS: These studies suggest that the differences in oxidative stress between human arteries and veins are unlikely to be caused by SOD activity. However SOD plays and important role in amelioration of oxidative stress in both types of vessels.